Controlling the Environmental Crisis through the Local Wisdom Approach of Kampung Naga from an Islamic Perspective - Munajar, Adhi; Rahmah, Rahmah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The environmental crisis caused by modernization and the exploitation of natural resources calls for alternative approaches to sustainable ecosystem management. One approach that has endured to this day is the local wisdom of indigenous communities. The Naga Traditional Village in Tasikmalaya, West Java, is an example of a community that has been able to maintain environmental balance through a cultural value system integrated with Islamic teachings. Traditions of taboos, Sundanese proverbs, and customary practices passed down through generations form the ethical foundation for maintaining a harmonious relationship between humans, nature, and God. This study aims to analyze the forms of local wisdom of the Naga Village community in environmental management and to examine its integration with Islamic values in building ecological ethics and character education. This study uses a qualitative approach with a descriptive-analytical method. The data was obtained through a literature review, observations of community cultural practices, and an analysis of traditional values, Sundanese proverbs, and the spatial management system in place in Kampung Naga. The research findings indicate that the concept of pamali functions as a social and spiritual mechanism for preserving the ecosystem. The territorial zoning system, comprising sacred, clean, and unclean areas, along with customary rules regarding the use of forests and water sources, creates a pattern of sustainable environmental management. These values are reinforced by Islamic principles such as khalifah fil ardh, ihsan, and qana’ah, which emphasize human responsibility toward nature. These findings enrich the study of Islamic eco-theology by demonstrating that local wisdom can serve as a tangible form of religion-based environmental ethics integrated into community cultural practices. The local wisdom model of Kampung Naga can serve as a reference for the development of environment-based character education, community-based conservation policies, and contributions toward achieving the Sustainable Development Goals, particularly quality education, climate action, and the protection of terrestrial ecosystems.